Self-Confidence upon Nursery Children in Al-Mahaweel with some Variables at the Babylon City (Medico Legal Update, 2019)
This study is a descriptive study to assess the level of self-confidence in kindergartens in Babylon . Thestudy sample included 50 children with (30) male and (20) female This study was conducted in the provinceof Babylon in the Mahaweel district – the Imam City in the kindergarten Masoudi for the semester 2016-2017 , The sample collection period was extended from December 2016 to January 2017. Design of thestudy : Descriptive study , setting of the study : The study was conducted in the province of Babylon in theMahaweel district , Time of the study : The Semester 2016 - 2017 , the sample of study : The sample wasselected in Al-Masoudi kindergarten in Al-Imam district , The study consisted of (50) children, males (30)and females (20). The results of the study showed a difference in the level of self confidence in childrenthrough the results of questionnaires, which were based on four fields : motor skills, self-reliance, socialskills and physical appearance and included the age of children and level of education for the father andmother.